Will AI Enable Telepathic Medical Communication? Decoding the Future of Digital Health - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
Will AI Enable Telepathic Medical Communication? Decoding the Future of Digital Health The concept of telepathy—the direct communication of thoughts wit...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care